Integration of Free Nutritious Meal Programs with Primary Health Services - Sella Elita Sembiring; Muhammad Tsawaby Hasian; Hana Isal Salina Ginting (International Journal of Medicine And publich Health, 2026)
School feeding programs have been shown to improve educational participation and children’s nutritional status. Indonesia’s Free Nutritious Meals (MBG) program represents a major investment in human capital development. However, without integration with primary health care, its long-term health impact may be limited. This study proposes a policy model integrating MBG with community health center (puskesmas) services using a health systems and Theory of Change approach. A conceptual-analytic review of international literature (2010–2024) was conducted. The proposed model includes screening for anemia, nutritional monitoring, referral systems, and digital data integration. Comparative analysis of Brazil and India indicates that cross-sector integration enhances program sustainability and population health outcomes. Integrating MBG with primary health care may improve cost-effectiveness, strengthen the health system, and accelerate human capital development in Indonesia.